View of Shiva Temple 1 - Temples of India Project Team (Jio Institute, 2024)
Shiva Temple 1 is situated near the revered banyan tree. The temple is a small structure with an antarala (vestibule or antechamber) and a garbhagriha (sanctum sanctorum). The shikhara (superstructure) of the temple is in ruins.